Encyclopedia of Social Welfare History in North America. - Herrick, Dr. John M. M. (SAGE Publications, 2004)
The Encyclopedia of Social Welfare History in North America is a unique reference book that provides readers with basic information about the history of social welfare in North America, including Canada, Mexico, and the United States. Since many themes and issues are similar in the three nations, entries provide comparative information about common as well as distinctive concerns and developments. Significant events, influential people, legislation, social problems, and societal responses are described in detail. Editors include specialists in the social welfare history of each nation, and the.